2004
DOI: 10.1523/jneurosci.4056-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant and Antiepileptogenic Effects Mediated by Adeno-Associated Virus Vector Neuropeptide Y Expression in the Rat Hippocampus

Abstract: Neuropeptide Y (NPY) inhibits seizures in experimental models and reduces excitability in human epileptic tissue. We studied the effect of long-lasting NPY overexpression in the rat hippocampus with local application of recombinant adeno-associated viral (AAV) vectors on acute kainate seizures and kindling epileptogenesis.Transgene expression was significantly increased by 7 d, reached maximal expression by 2 weeks, and persisted for at least 3 months. Serotype 2 AAV vector increased NPY expression in hilar in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
170
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(184 citation statements)
references
References 58 publications
12
170
1
1
Order By: Relevance
“…Accordingly, increased NPY expression in the hippocampus after prenatal betamethasone exposure is congruent with anti-anxiety effects. Increased expression of NPY (which also has anticonvulsant features; Richichi et al, 2004) in the hippocampus may also help in explaining the slower dentate gyrus kindling rate in betamethasone-exposed immature rats compared to saline-exposed rats in our previous study (Velíšek, 2005b). Earlier studies have shown that mainly ventral but also dorsal hippocampus is involved in anxiety control (Andrews et al, 1997;Bannerman et al, 2002aBannerman et al, , b, 2003Gonzalez et al, 1998;Kjelstrup et al, 2002;McHugh et al, 2004) and NPY alterations in the hippocampus affect anxiety behaviors (Heilig, 2004;Thorsell et al, 2000).…”
Section: Technical Considerationsmentioning
confidence: 62%
“…Accordingly, increased NPY expression in the hippocampus after prenatal betamethasone exposure is congruent with anti-anxiety effects. Increased expression of NPY (which also has anticonvulsant features; Richichi et al, 2004) in the hippocampus may also help in explaining the slower dentate gyrus kindling rate in betamethasone-exposed immature rats compared to saline-exposed rats in our previous study (Velíšek, 2005b). Earlier studies have shown that mainly ventral but also dorsal hippocampus is involved in anxiety control (Andrews et al, 1997;Bannerman et al, 2002aBannerman et al, , b, 2003Gonzalez et al, 1998;Kjelstrup et al, 2002;McHugh et al, 2004) and NPY alterations in the hippocampus affect anxiety behaviors (Heilig, 2004;Thorsell et al, 2000).…”
Section: Technical Considerationsmentioning
confidence: 62%
“…Indeed NPY is an inhibitory neuromodulator, whose synthesis is prompted by seizures (Vezzani and Sperk, 2004), and is thus considered as part of an endogenous antiepileptic mechanism (Richichi et al, 2004). Accordingly, here NPY expression increased in the temporal cortex of naïve marmosets as a consequence of repetitive PTZ administration, inherent to the drug testing protocol.…”
Section: Discussionmentioning
confidence: 88%
“…During (University of Auckland, Auckland, New Zealand). Production of rAAV-NPY has been described previously (During et al, 2003;Richichi et al, 2004). Per site, 1 l of virus (1 ϫ 10 8 genomic copies) was injected over 5 min, after which the needle was kept in place for 10 min before removal.…”
Section: Methodsmentioning
confidence: 99%